DIGITALISASI BAHAN AJAR SUPPLEMENTARY BERBASIS AJARAN TRI-N UNTUK MENGEMBANGKAN KOMPETENSI BAHASA INGGRIS SISWA SEKOLAH DASAR - mariana srirahayu; Siti Rochmiyati; Banun Havifah Cahyo Khosiyono (Universitas Sarjanawiyata Tamansiswa, 2023)
The purposes of this study were to: (1) describe the analysis of the digital teaching materials needed in Tri-N teaching-based learning to develop English language proficiency in elementary schools; (2) describe the feasibility of digital teaching materials based on Tri-N teachings from experts and stakeholders; and (3) describe digital teaching materials based on Tri-N teachings that are efficient for improving elementary students' English competence. A new English learning tool and instructional materials were developed as part of this study. The development approach, often known as research and development (R&D), is being used in this qualitative and quantitative research. Interviews, questionnaires, and observation were the tools employed. Students in grades 5 at SDN Planjan II, SDN Planjan 1, and SDN Monggol served as the research subjects. The development model of Borg & Gall (2003: 775) served as the foundation for the research methods. The study's development process was divided into 10 stages, including research and data gathering, planning, development of the initial form of the product, initial field trials, product revision, field trials, operational product revisions, operational field trials, final product revisions, and dissemination. The results of this research show (1) an analysis of the need for digital teaching materials in Tri-N teaching-based learning to develop English language competence in elementary schools is very necessary. (2) RPP and digital supplementary teaching materials based on Tri-N teachings to be used as teaching materials for extracurricular English activities in elementary schools are feasible based on validation results by 1 expert and 2 stakeholders. The average score obtained was a percentage of 88.6% from expert validation which was categorized as